Study on Cooling System for Parked Cars using Mini Air Cooler and Exhaust Fan - Bagiyo Condro Purnomo; Indra Chandra Setiawan; Heru Adi Nugroho (Universitas Muhammadiyah Magelang, 2020)
Deaths among children and pets, as well as damage to car interior components, have been widely reported as a result of parking under direct sunlight for a long time. Rising car cabin temperatures in this condition trigger the formation of benzene gas, but it is not possible to turn on the AC due to security and energy consumption. Therefore, this article reports the experimental study on cabin cooling system for parked car under direct sunlight by applying a mini air cooler and exhaust fan powered by a solar cell on small car Bajaj Qute RE60. Two thermocouples were installed inside and outside the cabin to monitor the temperature for 7 hours, expressing daytime heat conditions. The results showed that this cooling system could reduce the temperature to 10 K by removing 8982 kJ (0.356 kW) of heat. In conclusion, this prototype is very promising to be developed and if implemented on a larger scale will reduce car interior damage while parking under direct sunlight.